Silicon carbon material, preparation method thereof, pole piece, application and lithium ion battery
By co-deposition of silicon sources and lanthanide compounds on porous carbon to form a core body and deposition of gas-phase carbon sources, silicon carbon materials with core-shell structures were prepared, which solved the problem of insufficient rate performance, capacity performance and circulation performance in lithium-ion batteries in existing silicon carbon materials, and achieved better battery performance.
Patent Information
- Application Number
- CN202411876442.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-25
AI Technical Summary
Existing silicon carbon materials have problems with insufficient rate performance, capacity performance and cycle performance in lithium-ion batteries, especially during repeated cycle expansion, which can easily lead to damage to nanoparticles, affecting conductivity and rate performance.
By performing the first vapor deposition on porous carbon, a silicon source and a lanthanide compound are co-deposition to form a core body, and then a second vapor deposition is performed. The vapor phase carbon source is further deposited to form a silicon carbon material with a core-shell structure.
This silicon carbon material can take into account excellent rate performance, capacity performance and cycle performance, significantly improving the overall performance of lithium-ion batteries.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon material and a preparation method, a pole piece, an application and a lithium-ion battery thereof. Background Art
[0002] Silicon-carbon negative electrode materials have attracted widespread attention due to their ultra-high gram capacity (when the silicon content is 50%, its gram capacity can generally reach 1900mAh / g). Its high tap density, high first efficiency, and high lithium insertion potential make it an indispensable negative electrode material for current ultra-high energy density batteries. Due to its large lithium insertion expansion, it is generally believed that its volume expansion can reach 300%. Repeated cyclic expansion can easily lead to the breakage of nanoparticles. Therefore, it is often sintered into amorphous nano or even sub-nano particles to inhibit its breakage during repeated expansion. There are many main reasons, one of which is that when the material particles are extremely small, even if repeated lithium insertion will cause partial stress concentration, but because the specific surface area of nanomaterials is extremely high and the surface energy is extremely high, its extremely high surface energy can effectively inhibit the breakage of silicon particles. The second is to lower the sintering temperature and make it an amorphous structure, in which the Si-H bonds that are not completely decomposed can make the material as a whole present an amorphous structure. Although it can greatly inhibit the breakage of silicon nanoparticles, it will reduce the initial efficiency of the material to a certain extent. More importantly, it affects the conductivity of silicon nanoparticles. The impact on conductivity is mainly reflected in the impact on ohmic resistance while also affecting ion diffusion resistance, which in turn affects the rate performance of the material, making it difficult to meet the current requirements for rate performance. Ohmic resistance is mainly reflected in the impact on the transmission of electrostatic force and then on lithium ion migration, while ion diffusion directly affects the transmission of lithium ions. Its rate is generally only half of that of traditional graphite batteries, that is, 3c devices with higher rates usually require two batteries to meet the requirements, which is obviously difficult to meet future development needs.
[0003] Generally speaking, wrapping carbon nanotubes on the surface of the silicon negative electrode with relatively high resistance can balance the electrostatic force conduction on the silicon negative electrode substrate to a certain extent and thus improve the fast charging speed and energy density to a certain extent, but the performance is extremely limited. Summary of the invention
[0004] In order to solve the above problems existing in lithium-ion batteries obtained from existing silicon-carbon materials, the present invention provides a silicon-carbon material and its preparation method, pole piece, application and lithium-ion battery. The lithium-ion battery obtained by using the silicon-carbon material as the negative electrode material can have excellent rate performance, capacity performance and cycle performance.
[0005] In order to achieve the above technical objectives, the present invention adopts the following technical solutions.
[0006] The present invention provides a method for preparing a silicon-carbon material, which comprises the following steps:
[0007] S1, performing a first vapor deposition on porous carbon to obtain a core body, wherein the gas source of the first vapor deposition includes a silicon source and a lanthanide compound, and the silicon source and the lanthanide compound are introduced simultaneously;
[0008] S2. Performing a second vapor deposition on the core body to obtain the silicon-carbon material; wherein the gas source of the second vapor deposition includes a gas-phase carbon source.
[0009] Preferably, in step S1, the difference between the decomposition temperatures of the silicon source and the lanthanide compound is 300° C. or less.
[0010] In the present invention, the lanthanide compound may be a lanthanide compound conventionally used in the art, which is introduced in gaseous form at the temperature of the first vapor deposition, and is preferably an organic lanthanide compound and / or an inorganic lanthanide compound.
[0011] In some embodiments, the lanthanide compound is an inorganic lanthanide compound, and the inorganic lanthanide compound is preferably one or more of nitrate M, sulfuric acid M, acetic acid M and citric acid M, for example, nitrate M, wherein M is a lanthanide element.
[0012] In some preferred embodiments, the lanthanide compound is M nitrate; the lanthanide compound is one or more of lanthanum nitrate, cerium nitrate, praseodymium nitrate, neodymium nitrate, promethium nitrate, samarium nitrate, europium nitrate, gadolinium nitrate, terbium nitrate, dysprosium nitrate, holmium nitrate, erbium nitrate, thulium nitrate, ytterbium nitrate and lutetium nitrate, for example, gadolinium nitrate, cerium nitrate or lutetium nitrate.
[0013] In some preferred embodiments, the lanthanide compound is M citrate, such as gadolinium citrate.
[0014] In some preferred embodiments, the lanthanide compound is M acetate, such as gadolinium acetate.
[0015] In the present invention, the lanthanide element in the lanthanide compound is preferably one or more of gadolinium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, for example, gadolinium, lutetium or cerium.
[0016] In step S1, the mass ratio of the silicon source to the lanthanide compound is preferably 4:(0.005-0.05), more preferably 4:(0.01-0.04), for example, 4:0.01, 4:0.02, 4:0.03 or 4:0.04.
[0017] In step S1, the gas source for the first vapor deposition preferably further includes a vapor phase compound containing a third main group element.
[0018] The gas phase compound containing the third main group element is preferably a boron source. The boron source is preferably borane. The borane is preferably one or more of borane, nested borane, reticular borane, open reticular borane and linked borane, for example, one or more of diborane, tetraborane and borane.
[0019] The mass ratio of the silicon source to the gas phase compound containing the third main group element is preferably 4:(0.0005-0.005), more preferably 4:(0.001-0.0025), for example 4:0.001, 4:0.0015, 4:0.002 or 4:0.0025.
[0020] In step S1, the gas source for the first vapor deposition preferably further includes a vapor phase compound containing a fifth main group element.
[0021] Wherein, the gas phase compound containing the fifth main group element is preferably a nitrogen source and / or a phosphorus source.
[0022] In some preferred embodiments, the phosphorus source is one or more of phosphine, diphosphine, sodium dihydrogen phosphate, tripotassium phosphate, phosphorus pentoxide, sodium pyrophosphate, potassium pyrophosphate, dicyclohexyl (2,2-diphenyl-1-methylvinyl) phosphine and sodium metaphosphate, for example, phosphine.
[0023] In some preferred embodiments, the nitrogen source is a nitrate, such as gadolinium nitrate.
[0024] The mass ratio of the silicon source to the gas phase compound containing the fifth main group element is preferably 4:(0.005-0.05), more preferably 4:(0.01-0.04), for example 4:0.01, 4:0.02, 4:0.03 or 4:0.04.
[0025] In step S1, the silicon source may be a silicon source conventionally used for vapor deposition in the art, which is introduced in gaseous form at the temperature of the first vapor deposition. The silicon source is preferably silane; the silane is, for example, monosilane and / or disilane.
[0026] In step S1, the gas flow rate of the first vapor deposition gas source is preferably 5-15 g·kg -1 min -1 , for example, 5g·kg -1 min -1 .
[0027] In step S1, the temperature of the first vapor deposition may be 400-1000°C, preferably 500-800°C, for example, 500°C, 550°C, 600°C, 700°C or 800°C.
[0028] In step S1, the first vapor deposition time may be 4-10 h, for example, 5 h.
[0029] In step S1, the first vapor deposition is preferably performed under an inert atmosphere. Preferably, the mass ratio of the inert atmosphere to the gas source of the first vapor deposition is (70-90):(10-30), for example, 80:20 or 75:25.
[0030] In step S1, the particle size Dv50 of the porous carbon is preferably 4-20 μm, more preferably 6-10 μm, for example 7.8 μm.
[0031] In step S1, the (Dv90-Dv10) / Dv50 of the porous carbon is preferably (0.1-10):1, more preferably (0.5-2):1, for example 1:1.
[0032] In step S1, the specific surface area of the porous carbon is preferably 1000-3500m 2 / g, for example, 1854 m 2 / g.
[0033] In step S1, the specific surface area provided by the micropores of the porous carbon is preferably 70%-100%, for example 89%, where the percentage is the percentage of the specific surface area provided by the micropores to the total specific surface area of the porous carbon.
[0034] In step S1, the specific surface area provided by mesopores of the porous carbon is preferably 0-30%, more preferably 10%-20%, for example 11%, where the percentage is the percentage of the specific surface area provided by the mesopores to the total specific surface area of the porous carbon.
[0035] In step S1, the pore volume of the porous carbon is preferably 0.5-1.5 cm 3 / g, more preferably 1-1.5 cm 3 / g, for example, 1.32 cm 3 / g.
[0036] In step S1, the method for preparing porous carbon preferably comprises the following steps:
[0037] S0-1, firstly mixing a carbon source and a solvent to obtain a mixture, and then drying the mixture to obtain a porous carbon precursor;
[0038] S0-2. Carbonizing and activating the porous carbon precursor to obtain porous carbon.
[0039] In step S0-1, the carbon source may be a conventional carbon source in the art, preferably one or both of phenolic resin and asphalt. The asphalt is preferably asphalt that has been oxidized or surface-modified.
[0040] In some embodiments, the carbon source is a phenolic resin, and the mixture further includes a curing agent; the curing agent is, for example, hexamethylenetetramine; wherein the mass ratio of the phenolic resin to the curing agent is preferably 100:(1-20), for example, 100:6.
[0041] In step S0-1, the mixing can be carried out in a conventional mixing device in the art, such as a high-speed dispersing homogenizer. When the mixing is carried out in a high-speed dispersing homogenizer, the mixing time is preferably 30-100 min, such as 60 min.
[0042] The dispersion speed of the high-speed dispersion homogenizer is preferably 1500-2500 r / min, for example 2000 r / min.
[0043] In step S0-1, the solvent may be a solvent commonly used in the art, such as alcohol.
[0044] In step S0-1, the drying may be a drying method conventionally used in the art, preferably spray drying.
[0045] The spray drying temperature is preferably 90-180°C, for example 130°C.
[0046] The spray drying is preferably performed to a particle diameter of 4-20 μm, for example, 8 μm.
[0047] In step S0-1, the particle diameter of the porous carbon precursor is preferably 4-20 μm, for example 8 μm.
[0048] In step S0-1, before the carbonization treatment, a second drying treatment is preferably performed. The second drying treatment is preferably performed in a rotary kiln. The rotation speed of the rotary kiln is preferably 5-30 r / min, for example, 10 r / min.
[0049] The second drying process preferably takes 10-300 minutes and is carried out at a temperature of 100-300°C.
[0050] In step S0-2, the carbonization treatment is preferably performed by the following heating method: firstly heating to 150-250°C at 1-10°C / min, and then heating to 600-700°C at 1-10°C / min.
[0051] In some embodiments, the carbonization treatment is performed by the following heating method: firstly heating to 200° C. at 4° C. / min, and then heating to 652° C. at 4° C. / min.
[0052] In step S0-2, the carbonization treatment is preferably carried out in an inert atmosphere. The inert atmosphere generally includes an inert gas and / or nitrogen, such as nitrogen; the inert gas is, for example, argon. Preferably, the ventilation volume of the inert atmosphere is 10-20 L·kg -1 ·min -1 , for example, 14·L·kg -1 ·min -1 .
[0053] In step S0-2, the activation treatment is preferably carried out in carbon dioxide. Preferably, the ventilation volume of the carbon dioxide is 10-50 L·kg -1 ·min -1 , for example, 15·L·kg -1 ·min -1 .
[0054] In step S0-2, the temperature of the activation treatment is preferably 450-800°C, for example 550°C.
[0055] In step S0-2, the activation treatment time is preferably 5-15 h, for example 9 h.
[0056] In step S2, the gas-phase carbon source may be a gas-phase carbon source conventionally used for vapor deposition in the art, preferably one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene.
[0057] In step S2, the gas flow rate of the second vapor deposition gas source is preferably 0.5-5 g·kg -1 min -1 , for example, 2 g·kg -1 min -1 .
[0058] In step S2, the temperature of the second vapor deposition is preferably 400-1000°C, for example 500°C.
[0059] In step S2, the second vapor deposition time is preferably 5-20 h, for example, 10 h.
[0060] In step S2, the second vapor deposition is preferably performed under an inert atmosphere. Preferably, the mass ratio of the inert atmosphere to the gaseous carbon source is (70-90): (10-30).
[0061] In step S2, after the carbon is deposited, it is preferred to further include purging under an inert atmosphere, such as nitrogen.
[0062] The present invention provides a silicon-carbon material, which is prepared by the method for preparing the silicon-carbon material as described above.
[0063] The present invention provides a silicon-carbon material, which comprises a core-shell structure, wherein the core-shell structure comprises an inner core and an outer shell, wherein the inner core comprises porous carbon and a silicon layer located on the surface and in the pores of the porous carbon; the silicon layer is doped with lanthanide elements; and the outer shell comprises a carbon layer.
[0064] Preferably, the lanthanide element is one or more of gadolinium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, for example, gadolinium, cerium or lutetium.
[0065] Preferably, the silicon layer is further doped with a third main group element; wherein the third main group element is, for example, boron.
[0066] Preferably, the silicon layer is further doped with a fifth main group element; wherein the fifth main group element is, for example, nitrogen and / or phosphorus.
[0067] In the present invention, the content of lanthanide elements in the silicon-carbon material may be 10-10000 ppm, preferably 350-750 ppm, for example, 365 ppm, 387 ppm, 453 ppm, 432 ppm, 401 ppm, 475 ppm, 492 ppm, 501 ppm, 502 ppm, 532 ppm, 553 ppm, 550 ppm, 535 ppm, 561 ppm, 564 ppm, 587 ppm, 594 ppm, 623 ppm, 693 ppm, 601 ppm, 632 ppm, 682 ppm, 703 ppm, 721 ppm or 723 ppm.
[0068] In the present invention, the carbon content in the silicon-carbon material may be 40%-75%, for example, 45%, 44%, 47%, 49%, 50%, 53%, 51%, 56%, 55%, 59%, 67% or 71%, where the percentage is the mass percentage of the silicon-carbon material.
[0069] In the present invention, the content of silicon element in the silicon-carbon material may be 25%-60%, preferably 40%-60%, for example, 29%, 33%, 41%, 44%, 45%, 47%, 49%, 50%, 51%, 54%, 52%, 53%, 55% or 56%, where the percentage is the mass percentage of the silicon-carbon material.
[0070] In the present invention, the content of boron element in the silicon-carbon material may be 10-10000 ppm, preferably 450-600 ppm, for example, 485 ppm, 492 ppm, 501 ppm, 504 ppm, 512 ppm, 513 ppm, 518 ppm, 521 ppm, 523ppm, 524 ppm, 529 ppm, 532 ppm, 534 ppm, 538 ppm, 543 ppm, 546 ppm, 554 ppm, 556 ppm, 565 ppm, 567 ppm, 573 ppm or 587 ppm.
[0071] In the present invention, the content of nitrogen in the silicon-carbon material may be 10-10000 ppm, preferably 200-400 ppm, for example, 213 ppm, 224 ppm, 234 ppm, 242 ppm, 243 ppm, 253 ppm, 276 ppm, 279 ppm, 286 ppm, 291 ppm, 294 ppm, 296 ppm, 302 ppm, 315 ppm, 324 ppm, 326 ppm, 345 ppm, 349 ppm, 353 ppm, 286 ppm, 324 ppm, 368 ppm or 376 ppm.
[0072] In the present invention, the particle size Dv50 of the silicon-carbon material may be 5-20 μm, preferably 7-9 μm, for example, 7.9 μm, 8 μm, 8.1 μm, 8.2 μm or 8.3 μm.
[0073] In the present invention, (Dv90-Dv10) / Dv50 of the silicon-carbon material may be 0.1-10, for example, 1.2.
[0074] In the present invention, the specific surface area of the silicon-carbon material may be 0.1-100 m 2 / g, for example, 1.1 m 2 / g.
[0075] In the present invention, the specific surface area provided by the micropores of the silicon-carbon material may be 70%-100%, for example 86.7%, where the percentage is the percentage of the specific surface area provided by the micropores to the total specific surface area of the silicon-carbon material.
[0076] In the present invention, the specific surface area provided by the mesopores of the silicon-carbon material may be 0-20%, for example, 13.2%, where the percentage is the percentage of the specific surface area provided by the mesopores to the total specific surface area of the silicon-carbon material.
[0077] In the present invention, the electrical conductivity of the silicon-carbon material may be 0.1-10 S / m.
[0078] The present invention provides a pole piece, which comprises the silicon-carbon material as described above.
[0079] The present invention provides an application of the silicon-carbon material as described above as a negative electrode material in a lithium-ion battery.
[0080] The present invention also provides a lithium ion battery, which comprises the silicon-carbon material as described above.
[0081] On the basis of being in accordance with the common sense in the art, the above-mentioned preferred conditions can be arbitrarily combined to obtain the preferred embodiments of the present invention.
[0082] The reagents and raw materials used in the present invention are commercially available.
[0083] The positive and progressive effects of the present invention are:
[0084] In the preparation method of the silicon-carbon material of the present invention, a silicon source and a lanthanide compound are used for co-deposition in the first vapor deposition, and the obtained silicon-carbon material is used as a negative electrode material to obtain a lithium-ion battery with excellent rate performance, capacity performance and cycle performance. DETAILED DESCRIPTION
[0085] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0086] Example 1
[0087] 1. Preparation of silicon-carbon materials
[0088] S0. Preparation of porous carbon:
[0089] S0-1, 1kg of phenolic resin, 2kg of alcohol and 60g of hexamethylenetetramine (HMT) were mixed by high-speed homogenizer with a dispersion speed of 2000r / min for 60min. The mixture was spray dried at 130℃ until the Dv50 particle size was 8 μm;
[0090] S0-2, placing the spray-dried powder in a rotary furnace for cross-linking at a temperature of 200°C, a time of 60 minutes, and a rotation speed of 10 r / min;
[0091] Carbonization was then performed: the first stage temperature rise curve was 4°C / min, the temperature was raised for 50 min, and then the temperature was raised to 200°C and kept for 1 h, and the phenolic resin was cross-linked; the second stage temperature rise curve was 4°C / min, the temperature was raised for 113 min, and the nitrogen atmosphere was protected, and the ventilation volume was 1 L·kg -1 ·min -1 ;
[0092] Then, the activated samples were placed in a CO2 atmosphere for 9 h at a temperature of 550 °C and a ventilation volume of 2 L kg -1 ·min -1 , porous carbon (particle size Dv50 = 7.8 μm, (Dv90-Dv10) / Dv50 = 1, specific surface area of 1854 m 2 / g, the micropores provide a specific surface area of 89%, and the mesopores provide a specific surface area of 11%).
[0093] S1. Adjust the furnace temperature to 500°C, switch the atmosphere to a mixture of monosilane, diborane and gadolinium nitrate (the mass of the mixture accounts for 20% of the total mass of the atmosphere) and argon (the mass of argon accounts for 80% of the total mass of the atmosphere), and deposit at 500°C for 5 h to form nuclei. The ventilation rate of monosilane is 3.5 g min -1 kg -1 The ventilation rate of diborane is 0.0015 g·min -1 kg -1 The ventilation rate of gadolinium nitrate was 0.03 g·min -1 kg -1 , the ventilation rate of argon is 14g·min -1 kg -1 ;
[0094] S2. Then switch the atmosphere to an acetylene mixture (20% acetylene and 80% argon by mass), with an acetylene flow rate of 5 g kg -1 ·min -1 , and continue to deposit at 500°C for 10 hours; then switch the atmosphere to nitrogen for purging, and then cool to room temperature 25°C to obtain a silicon-carbon material.
[0095] On the basis of Example 1, the conditions of the remaining examples and comparative examples differ from those of Example 1 only in the specific parameters in Table 1, and the other conditions are the same as those of Example 1. In the first vapor deposition, the difference between the decomposition temperatures of the silicon source and the lanthanide compound is 300° C. or less. Specifically, when the silicon source is monosilane and when the lanthanide compound is gadolinium nitrate, the difference between the decomposition temperatures of the two is between 100-300° C.
[0096] Effect Example 1
[0097] The silicon-carbon materials prepared in the examples and comparative examples were subjected to relevant tests on particle size, element content and specific surface area, as follows:
[0098] (1) Dv50 particle size, Dv90 particle size and Dv10 particle size
[0099] The Dv50 particle size, Dv90 particle size and Dv10 particle size were tested respectively, and the testing equipment was a laser particle size analyzer.
[0100] Calculate (Dv90-Dv10) / Dv50.
[0101] (2) Silicon content and carbon content:
[0102] The carbon content and oxygen content are obtained by testing with a 100-carbon oxygen meter. Silicon content = 1-carbon content-oxygen content.
[0103] (3) Content of lanthanide elements, boron elements and nitrogen elements:
[0104] The contents of lanthanide, boron and nitrogen in silicon-carbon materials were tested using an inductively coupled plasma spectrometer (ICP, Agilent, model Agilent 5800).
[0105] (4) Specific surface area, specific surface area provided by micropores and specific surface area provided by mesopores: measured using Bestec NT-8000.
[0106] The above test results are shown in Table 2.
[0107] Effect Example 2
[0108] The silicon-carbon materials prepared in Examples 1-27 and Comparative Examples 1-6 are used as negative electrode materials to prepare negative electrode sheets. The preparation method of the negative electrode sheet comprises the following steps:
[0109] The negative electrode formula was designed as CMC: PAA: SBR: SP: CNTs: silicon-carbon material: graphite = 0.5: 2.5: 1: 0.1: 0.1: 8: 87.8 (by mass ratio). The negative electrode slurry preparation process was graphite → CMC → silicon-carbon material → SP → CNTs. After dispersing for 3 hours with a planetary disperser at a rotation speed of 300 r / min and a revolution of 1000 r / min, 80% deionized water was injected, and the mixture was dispersed at a speed of 500 r / min and a revolution of 600 r / min for 1 hour. PAA was added and dispersed at a rotation speed of 500 r / min and a revolution of 500 r / min for 1 hour. 20% deionized water was injected, and finally SBR was added and dispersed at a rotation speed of 300 r / min and a revolution of 300 r / min for 1 hour to obtain a negative electrode slurry (solid content of 40%).
[0110] The negative electrode current collector used was 8 μm thick copper foil. The negative electrode slurry was coated on both sides of the negative electrode current collector. The active material was coated on one side with a thickness of 40 μm and a compaction density of 1.7 g / cm 3 , wherein the coating speed is 40 cm / s, the baking temperature is 80° C., and the drying time is 400 s. The negative electrode slurry forms a negative electrode material layer.
[0111] Effect Example 3
[0112] The electrode sheet and the negative electrode material layer prepared in Example 2 were subjected to compression and conductivity tests. The specific test methods are as follows:
[0113] (1) Compacted density
[0114] Test method: Punch the pole piece into a unit circle, test the weight, subtract the copper foil weight, and divide by the thickness to get the density.
[0115] (4) Conductivity: Take 0.5g of the powder of the negative electrode material layer and add it to the test mold. After vibrating for 10 seconds, add the upper gasket. Place the test mold on the table of the electronic pressure testing machine and connect it to the resistivity tester. Increase the pressure of the electronic pressure testing machine to 6 MPa, keep the pressure constant for 60 seconds, then release the pressure to zero, read the sample deformation height and the value of the resistivity tester (the sample resistance). The conductivity is calculated according to the following formula σ=h / (S×R), where: σ is the powder conductivity of the negative electrode material layer, in S / cm; h is the sample deformation height, in cm; S is the sample bottom area, which is 3.14cm 2 ; R is the sample resistance, in Ω.
[0116] The above test results are shown in Table 2, Table 3 and Table 4.
[0117] Effect Example 4
[0118] Preparation of lithium-ion batteries:
[0119] (1) Preparation of positive electrode
[0120] Lithium cobalt oxide LCO: PVDF: SP: CNTs = 100: 1.3: 0.6: 1 (by mass ratio), the order and process of adding materials is LCO → SP → CNTs → PVDF, and the planetary disperser is used to disperse for 1 hour at a rotation speed of 800r / min and a revolution speed of 1000r / min, and NMP is added to obtain a mixture (solid content of 72%), and the mixture is dispersed for 4 hours at a rotation speed of 500r / min and a revolution speed of 500r / min and a vacuum degree of -0.9 to obtain a positive electrode slurry. The coated positive electrode current collector uses a 14 μm thick aluminum foil. The positive electrode slurry is coated on one side of the positive electrode current collector surface, the coating active material thickness is 40 μm, and the compaction density is 4.2 g / cm 3 , where the coating speed is 40 cm / s, the post-baking speed is 85°C, and the drying time is 400s.
[0121] (2) Electrolyte
[0122] Electrolyte formula: The formula of the mixed solvent is: EC 20%, PC 20%, DEC 30%, PP 30% (a total of 100 parts by mass); electrolyte: LiPF6 15%, the percentage is the mass percentage of the mixed solvent; additives: FEC 6%, PS 2.5%, LiODFB 0.5%, the percentage is the mass percentage of the mixed solvent.
[0123] (3) Battery assembly
[0124] The negative electrode sheet, separator and positive electrode sheet were assembled (the coated surface of the positive electrode sheet was facing the negative electrode sheet), and the electrolyte (0.5 mL) was added to assemble a CR2032 button battery. The full battery was a 100 mAh single-piece stacked battery; the separator was purchased from Enjie (model HSV7).
[0125] The full battery design N / P=1.1, N / P=gram capacity of negative electrode per unit area × efficiency of the first three cycles / gram capacity of positive electrode per unit area.
[0126] The positive electrode gram capacity is determined by using lithium cobalt oxide as the positive electrode and lithium sheet as the negative electrode. The current is 1mAh, the voltage window is 2.8V-4.4V, and the cut-off current is 0.05mAh.
[0127] Determination of the negative electrode gram capacity: the negative electrode sheet is the positive electrode, the lithium sheet is the negative electrode, and the discharge is continuous at a current of 1mAh. The voltage window is 0V-0.8V, and the reversible gram capacity is determined as the gram capacity.
[0128] Determination of the first efficiency: the negative electrode is the positive electrode, the lithium electrode is the negative electrode, and the discharge is continuous at a current of 1mAh. The voltage window is 0V-1.5V. The first efficiency is obtained by multiplying the coulomb efficiencies of the first three times.
[0129] The electrochemical properties of the CR2032 button cell obtained above were characterized as follows:
[0130] (1) First effect
[0131] The constant voltage discharge method was adopted, after discharging to 0.000 V at 0.1 V / h, it was charged to 1.5 V at 0.1 V / h, and the charge and discharge capacity was recorded. The first effect was obtained by the lithium removal capacity / lithium insertion capacity.
[0132] (2) Gram capacity
[0133] ① 0.1C 1.5V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000 V at 0.1V / h, charge it to 1.5V at 0.1V / h, record 0.1C of the charge capacity, reassemble a CR2032 button battery, perform constant current charge and discharge test with 0.1C of the charge capacity recorded, discharge it to 0V and then charge it to 1.5V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the 0.1C 1.5V gram capacity.
[0134] ② 0.1C 0.8V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000 V at 0.1V / h, then charge it to 0.8V at 0.1 V / h, record the charging capacity of 0.1C, reassemble a CR2032 button battery, and perform constant current charge and discharge test to record the charging capacity of 0.1C, discharge it to 0V and then charge it to 0.8V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the gram capacity of 0.1C 0.8V.
[0135] ③ 0.3C 1.5V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000V at 0.1V / h, charge it to 1.5V at 0.1V / h, record the charging capacity of 0.3C, reassemble a CR2032 button battery, perform constant current charge and discharge test with recording charging capacity of 0.3C, discharge it to 0V and then charge it to 1.5V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the 0.3C 1.5V gram capacity.
[0136] ④ 0.3C 0.8V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000 V at 0.1V / h, charge it to 0.8V at 0.1V / h, record the charging capacity of 0.3C, reassemble a CR2032 button battery, perform constant current charge and discharge test to record the charging capacity of 0.3C, discharge it to 0 V and then charge it to 0.8V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the gram capacity of 0.3C 8V.
[0137] ⑤ 0.5C 1.5V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000 V at 0.1V / h, then charge it to 1.5V at 0.1V / h, record the charging capacity of 0.5C, reassemble a CR2032 button battery, and perform constant current charge and discharge test to record the charging capacity of 0.5C, discharge it to 0V and then charge it to 1.5V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the 0.5C 1.5V gram capacity.
[0138] ⑥ 0.5C 0.8V gram capacity: First assemble a CR2032 button battery, then use constant voltage discharge method, discharge it to 0.000 V at 0.1V / h, charge it to 0.8V at 0.1V / h, record the charging capacity of 0.5C, reassemble a CR2032 button battery, and perform constant current charge and discharge test to record the charging capacity of 0.5C, discharge it to 0V and then charge it to 0.8V. After obtaining the capacity, use the capacity / mass of active material in the electrode to obtain the gram capacity of 0.5C 0.8V.
[0139] 0.1C 0.8V gram capacity ratio (%): 0.1C 0.8V gram capacity / 0.1C 1.5V gram capacity×100.
[0140] 0.3C 0.8V gram capacity ratio (%): 0.3C 0.8V gram capacity / 0.3C 1.5V gram capacity×100.
[0141] 0.5C 0.8V gram capacity ratio (%): 0.5C 0.8V gram capacity / 0.5C 1.5V gram capacity × 100.
[0142] (3) Ratio retention rate
[0143] ① 0.3C 1.5V rate retention rate (%) = 0.3C 1.5V gram capacity / 0.1C 1.5V gram capacity × 100.
[0144] ② 0.3C 0.8V rate retention rate (%) = 0.3C 0.8V gram capacity / 0.1C 0.8V gram capacity × 100.
[0145] ③ 0.5C 1.5V rate retention rate (%) = 0.5C 1.5V gram capacity / 0.1C 1.5V gram capacity × 100.
[0146] ④ 0.5C 0.8V rate retention rate (%) = 0.5C 0.8V gram capacity / 0.1C 0.8V gram capacity × 100.
[0147] (4) Number of cycles to failure
[0148] 0.5C 1.5V cycle failure number of cycles: first assemble a CR2032 button battery, and then use constant voltage discharge method, discharge it to 0.000V at 0.1V / h, then charge it to 1.5V at 0.1V / h, record the charging capacity of 0.5C, reassemble a CR2032 button battery, and perform constant current charge and discharge test at 0.5C with a charging capacity of 0.5C, repeatedly charge and discharge from 0V to 1.5V, record the discharge capacity, and terminate when the discharge capacity is 60% of the 0.5C 1.5V capacity, and record the number of cycles.
[0149] The above test results are shown in Table 3 and Table 4.
[0150]
[0151]
[0152]
[0153]
[0154] Note: “ / ” in Table 1 and Table 2 means that the condition parameter is not involved in the specific experiment.
[0155] It can be seen from Table 1, Table 2, Table 3 and Table 4 that in the preparation method of the silicon-carbon material of the present invention, the silicon source and the lanthanide compound are co-precipitated, and the lithium-ion battery prepared by the obtained silicon-carbon material as the negative electrode material can take into account excellent capacity performance, rate performance and cycle performance. Specifically, the 0.1C 0.8V gram capacity can reach more than 92% (above C), and the 0.3C 1.5V rate retention rate can reach more than 97% (above C). On this basis, the 0.5C 1.5V rate retention rate (%) can reach more than 92% (above D), the 0.1C 1.5V gram capacity can reach more than 1940 mAh / g (above B), the 0.1C 0.8V gram capacity can reach more than 1790 mAh / g (above C), the 0.3C 0.8V rate retention rate can reach more than 96% (above D), the 0.3C 0.8V gram capacity proportion can reach more than 91% (above D), and the 0.5C 0.8V rate retention rate can reach more than 92% (above D).
[0156] Compared with Example 24, in Comparative Example 1, only silicon deposition was performed without co-deposition of lanthanide compounds. The 0.1C 0.8V gram capacity ratio and 0.3C 1.5V rate retention rate of the lithium-ion battery were significantly deteriorated, and it was impossible to take into account both excellent capacity performance and rate performance.
[0157] Compared with Example 24, in Comparative Example 2, only silicon deposition was performed without co-deposition of lanthanide compounds. Although the 0.3C 1.5V rate retention rate of the lithium-ion battery was comparable, the 0.1C 0.8V gram capacity ratio was significantly reduced.
[0158] Compared with Example 24, in Comparative Examples 3-4, only silicon deposition was performed without co-deposition of lanthanide compounds. Although the 0.1C 0.8V gram capacity ratio of the lithium-ion battery was comparable, the 0.3C 1.5V rate retention was poor.
[0159] Compared with Example 1, in Comparative Examples 5-6, no co-deposition of lanthanide compounds was performed. Although the 0.1C 0.8V gram capacity of the lithium-ion battery was comparable, the 0.3C 1.5V rate retention was poor.
[0160] In Examples 24-27, gadolinium nitrate and silane are co-deposited, and nitrogen atoms and gadolinium atoms are co-deposited into silicon nanoparticles. The 0.5C 0.8V gram capacity of the prepared lithium-ion battery is relatively excellent, reaching more than 93%. This may be because N has better deposition dispersion in semiconductor silicon, its metallicity is stronger, it is difficult to bond with silicon, and it is mostly dispersed into silicon nanoparticles in the form of single atoms. When dispersed into silicon nanoparticles in the form of single atoms, it is more likely to cause silicon atoms to self-assemble into silane nanoparticles to form disorder, and because of its larger atomic radius, it can effectively widen the channel of the lattice fringes, facilitating the escape and embedding of lithium ions.
[0161] In Example 1 and Examples 6-23, when co-deposition of silane and gadolinium nitrate is performed, further doping with boron can further improve the conductivity of the silicon-carbon material, thereby further improving the rate performance of the obtained lithium-ion battery.
[0162] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that this is only for illustration and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: It includes the following steps: S1, performing a first vapor deposition on porous carbon to obtain a core body, wherein the gas source of the first vapor deposition includes a silicon source and a lanthanide compound, and the silicon source and the lanthanide compound are introduced simultaneously; S2. Performing a second vapor deposition on the core body to obtain the silicon-carbon material; wherein the gas source of the second vapor deposition includes a gas-phase carbon source.
2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: The lanthanide compound satisfies one or more of the following conditions ac: a. The difference between the decomposition temperatures of the silicon source and the lanthanide compound is 300° C. or less; b. The lanthanide compound is one or more of nitric acid M, sulfuric acid M, acetic acid M and citric acid M, for example, nitric acid M, wherein M is a lanthanide element; c. The lanthanide element in the lanthanide compound is one or more of gadolinium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, for example, gadolinium.
3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: Step S1 satisfies one or more of the following conditions an: a. In step S1, the mass ratio of the silicon source to the lanthanide compound is 4:(0.005-0.05), preferably 4:(0.01-0.04), for example, 4:0.01, 4:0.02, 4:0.03 or 4:0.04; b. In step S1, the gas source for the first vapor deposition further comprises a gas phase compound containing a third main group element; Wherein, the gas phase compound containing the third main group element is preferably a boron source; the boron source is preferably borane; wherein the borane is preferably one or more of borane, nested borane, reticular borane, open reticular borane and linked borane, for example, one or more of diborane, tetraborane and borane; The mass ratio of the silicon source to the gas phase compound containing the third main group element is preferably 4:(0.0005-0.005), more preferably 4:(0.001-0.0025), for example, 4:0.001, 4:0.0015, 4:0.002 or 4:0.0025; c. In step S1, the gas source for the first vapor deposition further comprises a gas phase compound containing a fifth main group element; Wherein, the gas phase compound containing the fifth main group element is preferably a nitrogen source and / or a phosphorus source; the phosphorus source is preferably one or more of phosphine, diphosphine, sodium dihydrogen phosphate, tripotassium phosphate, phosphorus pentoxide, sodium pyrophosphate, potassium pyrophosphate, dicyclohexyl (2,2-diphenyl-1-methylvinyl) phosphine and sodium metaphosphate, such as phosphine; the nitrogen source is preferably a nitrate, such as gadolinium nitrate; The mass ratio of the silicon source to the gas phase compound containing the fifth main group element is preferably 4:(0.005-0.05), more preferably 4:(0.01-0.04), for example, 4:0.01, 4:0.02, 4:0.03 or 4:0.04; d. In step S1, the silicon source is silane; the silane is, for example, monosilane and / or disilane; e. In step S1, the ventilation volume of the gas source for the first vapor deposition is 5-15 g·kg -1 min -1 , for example, 5 g·kg -1 min -1 ; f. In step S1, the temperature of the first vapor deposition is 400-1000° C., preferably 500-800° C., for example, 500° C., 550° C., 600° C., 700° C. or 800° C.; g. In step S1, the first vapor deposition time is 4-10 hours; h. In step S1, the first vapor deposition is performed under an inert atmosphere; preferably, the mass ratio of the inert atmosphere to the gas source of the first vapor deposition is (70-90):(10-30), for example, 80:20 or 75:25; i. In step S1, the particle size Dv50 of the porous carbon is 4-20 μm, preferably 6-10 μm, for example 7.8 μm; j. In step S1, (Dv90-Dv10) / Dv50 of the porous carbon is (0.1-10):1, preferably (0.5-2):1, for example, 1; k. In step S1, the specific surface area of the porous carbon is 1000-3500 m 2 / g, for example, 1854 m 2 / g; 1. In step S1, the micropores of the porous carbon provide a specific surface area ratio of 70%-100%, for example, 89%; m. In step S1, the mesopore ratio of the porous carbon is 0-30%, preferably 10%-20%, for example 11%; n. In step S1, the pore volume of the porous carbon is 0.5-1.5 cm 3 / g, preferably 1-1.5 cm 3 / g, for example, 1.32 cm 3 / g.
4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the second vapor deposition satisfies one or more of the following conditions ae: a. In step S2, the gaseous carbon source is one or more of alkynes, alkanes, olefins, aromatic compounds and carbohydrates, such as acetylene; b. In step S2, the gas flow rate of the second vapor deposition gas source is 0.5-5 g·kg -1 min -1 , for example, 2 g·kg -1 min -1 ; c. In step S2, the temperature of the second vapor deposition is 400-1000° C., for example, 500° C.; d. In step S2, the second vapor deposition time is 5-20 h, for example, 10 h; e. In step S2, the second vapor deposition is performed under an inert atmosphere; preferably, the mass ratio of the inert atmosphere to the gaseous carbon source is (70-90): (10-30).
5. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 4.
6. A silicon-carbon material, characterized in that: It comprises a core-shell structure, which comprises an inner core and an outer shell, wherein the inner core comprises porous carbon and a silicon layer located on the surface and in the pores of the porous carbon; the silicon layer is doped with lanthanide elements; and the outer shell comprises a carbon layer.
7. The silicon-carbon material according to claim 6, characterized in that: The silicon-carbon material satisfies one or more of the following conditions: a. The lanthanide element is one or more of gadolinium, lanthanum, cerium, praseodymium, neodymium, promethium, samarium, europium, terbium, dysprosium, holmium, erbium, thulium, ytterbium and lutetium, for example, gadolinium, cerium or lutetium; b. The silicon layer is further doped with a third main group element; wherein the third main group element is, for example, boron; c. The silicon layer is further doped with a fifth main group element; wherein the fifth main group element is, for example, nitrogen and / or phosphorus; d. The content of lanthanide in the silicon-carbon material is 10-10000 ppm, preferably 350-750 ppm, for example, 365 ppm, 387 ppm, 453 ppm, 432 ppm, 401 ppm, 475 ppm, 492 ppm, 501 ppm, 502 ppm, 532 ppm, 553 ppm, 550 ppm, 535 ppm, 561 ppm, 564 ppm, 587 ppm, 594 ppm, 623 ppm, 693 ppm, 601 ppm, 632 ppm, 682 ppm, 703 ppm, 721 ppm or 723 ppm; e. The carbon content of the silicon-carbon material is 40%-75%, for example, 45%, 44%, 47%, 49%, 50%, 53%, 51%, 56%, 55%, 59%, 67% or 71%, where the percentage is the mass percentage of the silicon-carbon material; f. The silicon content of the silicon-carbon material is 25%-60%, preferably 40%-60%, for example, 29%, 33%, 41%, 44%, 45%, 47%, 49%, 50%, 51%, 54%, 52%, 53%, 55% or 56%, where the percentage is the mass percentage of the silicon-carbon material; g. The boron content in the silicon-carbon material is 10-10000 ppm, preferably 450-600 ppm, for example, 485 ppm, 492 ppm, 501 ppm, 504 ppm, 512 ppm, 513 ppm, 518 ppm, 521 ppm, 523 ppm, 524 ppm, 529 ppm, 532 ppm, 534 ppm, 538 ppm, 543 ppm, 546 ppm, 554 ppm, 556 ppm, 565 ppm, 567 ppm, 573 ppm or 587 ppm; h. The content of nitrogen in the silicon-carbon material is 10-10000 ppm, preferably 200-400 ppm, for example, 213 ppm, 224 ppm, 234 ppm, 242 ppm, 243 ppm, 253 ppm, 276 ppm, 279 ppm, 286 ppm, 291 ppm, 294 ppm, 296 ppm, 302 ppm, 315 ppm, 324 ppm, 326 ppm, 345 ppm, 349 ppm, 353 ppm, 286 ppm, 324 ppm, 368 ppm or 376 ppm; i. The particle size Dv50 of the silicon-carbon material is 5-20 μm, preferably 7-9 μm, for example, 7.9 μm, 8 μm, 8.1 μm, 8.2 μm or 8.3 μm; j. (Dv90-Dv10) / Dv50 of the silicon-carbon material is 0.1-10, for example, 1.2; k. The specific surface area of the silicon-carbon material is 0.1-100 m 2 / g, for example, 1.1 m 2 / g; 1. The micropores of the silicon-carbon material provide a specific surface area ratio of 70%-100%, for example, 86.7%; m. The mesopore ratio of the silicon-carbon material is 0-20%, for example, 13.2%; n. The electrical conductivity of the silicon-carbon material is 0.1-10 S / m.
8. A pole piece, characterized in that: It comprises the silicon-carbon material as described in any one of claims 5-7.
9. Use of the silicon-carbon material as claimed in any one of claims 5 to 7 as a negative electrode material in a lithium-ion battery.
10. A lithium ion battery, characterized in that: It comprises the silicon-carbon material as described in any one of claims 5-7.